(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Kubanov R. А. An improvement of quality of professional preparation of future specialists of economic specialities is in the conditions of the credit-module departmental teaching. This paper discusses various approaches regarding the improvement of the quality of professional training of future specialists of economic specialties in terms of credit-modular system. Analyzes the essence of the concept of «quality of training future specialists of economic specialties». Designated the main elements of credit-modular organization of training for future use in the practice of a high school teacher.